Ethical Guidelines for the Use of AI in Students’ Assignments, Research, and Academic Writing - Barthomius K. Jiu; Iwan Bambang (PT Publikasiku Academic Solution, 2026)
This article examines the ethics of using generative artificial intelligence (Gen AI) in student assignments, research, and academic writing. The study was designed as a Systematic Literature Review (SLR) following the logic of PRISMA 2020. The review synthesizes official policy documents and peer-reviewed studies published primarily between 2023 and 2025, a period during which Gen AI became a major issue in higher education. The findings indicate that Gen AI should neither be treated as an absolute threat nor as a substitute for academic reasoning. Ethically acceptable use lies in transparent, limited, and accountable assistance, such as idea mapping, language refinement, conceptual clarification, and feedback support, while core academic responsibilities must remain under human control. The main ethical risks include plagiarism through concealment, fabricated references, hallucinated facts, privacy breaches, authorship confusion, deskilling, and inequality caused by unequal access and varying levels of AI literacy. This article argues that ethical governance in higher education should shift from a prohibition paradigm toward a guided and responsible-use paradigm grounded in honesty, verification, authorship accountability, pedagogical alignment, and institutional disclosure. The study also proposes a practical framework for universities and lecturers to classify permitted, restricted, and prohibited uses of Gen AI in academic work.